2010
DOI: 10.1038/ajg.2009.759
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Following Infliximab Therapy in Children With Ulcerative Colitis

Abstract: In this cohort of children with UC receiving infliximab, corticosteroid-free inactive disease was observed in 38 and 21% of patients at 12 and 24 months, respectively. By 24 months, 61% of patients had avoided colectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
2
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(84 citation statements)
references
References 21 publications
7
69
2
6
Order By: Relevance
“…Clinical series in pediatric patients with moderate-severe, refractory ulcerative colitis have described very similar results to series enrolling adult patients with approximately 50% of patients avoiding a colectomy within five years of initiating infliximab [17][18][19][20][21] .…”
Section: Anti-tnf Therapies In Moderate-severe Refractory Ulcerativesupporting
confidence: 53%
“…Clinical series in pediatric patients with moderate-severe, refractory ulcerative colitis have described very similar results to series enrolling adult patients with approximately 50% of patients avoiding a colectomy within five years of initiating infliximab [17][18][19][20][21] .…”
Section: Anti-tnf Therapies In Moderate-severe Refractory Ulcerativesupporting
confidence: 53%
“…Follow up of these cohorts also reported a drop in the rate of colectomy (67%) versus placebo (27%) [Janerot et al 2005]. Clinical series in pediatric patients with moderate to severe refractory UC have described very similar results to series enrolling adult patients with approximately 50% of patients avoiding colectomy within 5 years of initiating IFX [Hyams et al 2010;Russo et al 2009;Wilhelm et al 2008;Jakobovits et al 2007]. In the settings of severe-fulminant UC, cyclosporine has been (although controversial) described as salvage therapy for patients who have failed a course of intravenous steroids [McDonald et al 2005;Hanauer et al 2005].…”
Section: Introductionsupporting
confidence: 55%
“…A number of studies have confirmed that infliximab is safe and effective in the treatment of IBD in children (36,37). In China, infliximab is mostly used in patients with refractory IBD.…”
Section: A B C Dmentioning
confidence: 99%